Antioxidant potential of ethanol, ethyl acetate, n-hexane extracts from leaves, fruits, stems, and roots of red okra (Abelmoschus esculentus) - Putri, Salsabilla Wiyana; Hapsari, Lukiteswari Dyah Tri; Junairiah; Wahyuningsih, Sri Puji Astuti (Biogenesis: Jurnal Ilmiah Biologi, 2024)
Abelmoschus esculentus L. Moench has been known for its abundant and affordable antioxidant potential. This plant has different antioxidant levels regarding the parts of the plant. Red okra is rich in flavonoids and polyphenols, including strong antioxidant as quercetin ad anthocyanin. This research is intended to determine the IC50 value and compare the total content of phenolic and flavonoid from ethanol, ethyl acetate, and n-hexane extract of red okra (A. esculentus) leaves, fruits, stems, and roots. Extraction process was done by gradual maceration method using ethanol, ethyl acetate, and n-hexane. IC50 value interprets the antioxidant activity obtained from DPPH test. The results showed a very strong antioxidant activity from red okra stem extract with IC50 of 25.22 ppm and the lowest from fruit n-hexane extract with 821.55 ppm. From TPC test, the highest content was obtained from stem ethanol extract with 156.01 mg GAE/g and the lowest from stem n-hexane extract with 25.99 mg GAE/. From TFC test, the highest content was obtained from fruits ethanol extract with 108.15 mg QE/g and the lowest from stem ethanol extract with 2.26 mg QE/g. In conclusion, this research showed that red okra (A. esculentus) contains a high level of phenol and flavonoid compound and the highest antioxidant content was shown in ethanol extract.